Comunicação da informação em saúde: um panorama pós-pandêmico de (des)informação - Assis, Stella Schwanz Dias de (2023)
In the context of a pandemic, which began in 2020, due to the contagion of Covid-19, the importance of communicating health information was highlighted, especially in a context of crisis. The new coronavirus pandemic has highlighted the importance of carrying out studies on communication and health information, since it has shown the influence that these strategies, or the lack of them, can exert in times of crisis in public health. Since then, several studies have been developed around this theme, highlighting some concepts such as infodemic and disinformation. With that in mind, the general objective of the dissertation is to analyze the effects of communicating health information regarding vaccination, during the pandemic caused by Covid-19, on the informational behavior of Twitter users. To this end, we seek to identify concepts and definitions related to the communication of health information; understand the need for production and access to health information during the pandemic period and; identify the effects of communication of (mis)information in the health area, especially regarding vaccination, during the period of the Covid-19 pandemic. Working with the content analysis methodology, with the support of Network Analysis and Text Analysis for processing the data collected on Twitter. From the results, a great influence was observed not only on the themes that directly addressed the communicated information, but as a motivation for other connected or direct discussions to the associated arguments.